Prospective comparative study between peroneus longus tendon autograft and hamstring tendons autograft in single bundle ACL reconstruction - Mohamed Ali; Mohamed El-Shafie; Mohamed El-Sheikh; Ahmed Waly (Alexandria Journal of Medicine)
Background ACL reconstruction is often regarded as the most effective approach of restoring knee stability. Several graft possibilities are available, including (BPTB), four-strand hamstring autografts, quadriceps tendon, and peroneus longus tendon. Each has both advantages and cons. This study compares the effectiveness of peroneus longus and hamstring tendon autografts for single bundle ACL restoration.Patients and Methods The study involved 60 patients. Thirty of them had their torn anterior cruciate ligaments reconstructed arthroscopically using hamstring tendons, while the other 30 had their ACLs managed arthroscopically with peroneus longus tendon. The follow-up period lasted at least 12 months. Patients were assessed using IKDC score and Lysholm score. Ankle function was assessed using AOFAS score.Results There was a statistically significant difference in preoperative and postoperative range of motion improvement in each group as an IKDC score item. However, no statistically significant difference existed between both groups. A statistically significant change in Lysholm scores preoperatively and postoperatively in each group was detected, but there was no statistical difference between groups 1 and 2, either in terms of improvement or percentage improvement. The AOFAS score was used also to assess for any donor site morbidity. No significant difference was detected between both ankles range of motion and no ankle joint dysfunction or problems with sports activities.Conclusion The current study found that the PL tendon autograft might be considered a safe, effective and a technically easy graft option for ACLR. The research shows no substantial difference in postoperative knee stability or graft failure rate between hamstring and peroneus tendons.